2003
DOI: 10.1002/mpo.10314
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Epstein‐Barr virus‐associated hemophagocytic lymphohistiocytosis (EBV‐HLH) in young adults: A report from the HLH studyl center

Abstract: Patients receiving etoposide within four weeks after diagnosis had a good prognosis as five of the seven patients survived compared to one of 13 not treated with etoposide or treated late (chi-square test for survival, P = 0.0095). The Kaplan-Meier analysis showed the 2.5-year survival of 85.7 +/- 13.2% in the early etoposide-treated patients, compared to 10.3 +/- 9.4% in the remaining patients (log-rank test, P = 0.0141). Thus, early etoposide treatment is effective in treating EBV-HLH in young adults as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 31 publications
1
79
0
2
Order By: Relevance
“…5 In young adult patients, Imashuku et al reported that treatment with etoposide within four weeks of diagnosis was extremely effective in improving the outcome of EBV-HLH. 6 In the current case, we could not control hypercytokinemia despite the multiple combination therapy.…”
Section: Discussionmentioning
confidence: 62%
“…5 In young adult patients, Imashuku et al reported that treatment with etoposide within four weeks of diagnosis was extremely effective in improving the outcome of EBV-HLH. 6 In the current case, we could not control hypercytokinemia despite the multiple combination therapy.…”
Section: Discussionmentioning
confidence: 62%
“…However, in some cases of HLH, the initiating cause is not identified. Because of its heterogeneous etiology and nonspecific clinical and laboratory findings which often mimic other conditions like sepsis, the diagnosis of secondary HLH may be delayed or unrecognized [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…All current studies on the treatment of adults are noncontrolled and retrospective small-sample studies, 16,[24][25][26] and this study provides encouraging results for the salvage therapy of refractory HLH. Our study might bridge the transition from induction therapy to etiology therapy.…”
Section: Discussionmentioning
confidence: 69%